An Experimental Study on Irradiated Interface of Silicon - Lamsal, Min Raj (Himalayan Physics, 2020)
Atomic Force Microscopic (AFM) studies of Mega electron-volt (MeV) ions irradiated silicon surface morphology has been studied to a ﬂuence of 5 x 108 ions/cm2. Interesting features of cracks of 50 nm in depth and 100 nm in width have been observed on the irradiated surface. The features seemed to have been caused by the irradiation-induced stress in the irradiated regions of the target surface. The observed feature of crack seems to be mainly due to the high electronic energy loss of the irradiated ions on the surface that induces the stress in it. It conﬁrms that the coarseness of the microstructure of a material directly affect the mechanical properties.